The Leadership Contract : The Fine Print to Becoming a Great Leader - Molinaro, Vince, 1962- (Hoboken John Wiley, 2013)
Establish the terms and conditions of a "Leadership Contract" to ensure the success of your company Recent studies show that only 7 percent of employees have trust and confidence in their senior leaders
Include Index
Keywords: Organizational change -- Leadership